KOBALAMIN, KOBALAMIN-ANALOG DAN KEBERADAANNYA DALAM TEMPE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
Analytical Methods Committee, 1956. The estimation of vitamin 8-12. Ana lyst. 81:132. AOAC. 1980. Official Methods of Analysis. 13th ed., Assn. Offic. Anal. Chem., Washington, D.C. Beuchat, L.R. 1984. Fermented soybean foods. Food Tech. 36:64. Chanarin, I., 1968. The megaloblastic anemias, Blackwell, Oxford. Chung, H.J., and Fields, M.L. 1986. Production of riboflavin and vitamin B-12 by Bacillus megaterium ATCC 13639 and Acetobacter aerogenes in corn meal. J. Food Sci. 51:1514. Djurtoft, R., and Nielsen, J,P. 1983. Increase in some B vitamins, including 13-12, during fermentation of tempeh, produced from cowpeas or soybeans.